White Extremism: A Brief Review on Origin, Behavior Indicators, and Religious Beliefs - Sukabdi, Zora A. (Journal of Ecohumanism, 2024)
Whiteness is fluid, as who is considered ‘white’ changes over time. Like race, whiteness is socially and politically constructed. Whiteness does not just refer to skin color; however, it is an ideology based on beliefs, values, behaviors, habits, and attitudes, which result in the unequal distribution of power and privilege based on skin color. White supremacy is defined as beliefs and ideas claiming the natural superiority of the lighter-skinned, or ‘white’, human races over other racial groups. Using a literature review, this article explores the brief history of humans’ ‘whiteness’, indicators of white extremism, and belief systems justifying white extremism. The findings reveal that humans’ whiteness has been evident since around 80,000 years ago. Moreover, white extremism’s obvious indicator is when violence is used as the only means to achieve goals, on top of other indicators. Extremism comprises radicalism, while radicalism does not always include extremism. Further, the beliefs of white supremacy may have been rooted in the story of Noah’s and Abraham’s children. These findings may help academics and practitioners understand white extremism through psychological and ideological perspectives.